Severe chronic obstructive pulmonary disease is associated with reduced oral health conditions - Ciardo, Antonio; Simon, Marlinde M.; Eberhardt, Ralf; Brock, Judith; Ritz, Alexander; Kim, Ti-Sun (Oral diseases, 2023)
Objectives This study aimed to investigate the association of explicitly severe chronic obstructive pulmonary disease (COPD) with oral conditions considering in-depth shared risk factors. Methods A case-control study was conducted with 104 participants, 52 with severe COPD and 52 matched controls without COPD. Dental and periodontal status were clinically assessed and oral health-related quality of life (OHRQoL) by OHIP-G14-questionnaire. Results Between COPD- and control-group, there were no statistically significant differences regarding age (66.02 ± 7.30), sex (female: 52 [50%]), smoking history (44.69 ± 23.23 pack years) and number of systemic diseases (2.60 ± 1.38). COPD patients demonstrated significantly fewer remaining teeth (12.58 ± 9.67 vs. 18.85 ± 6.24, p < 0.001) besides higher DMFT (decayed, missing and filled teeth) index (21.12 ± 5.83 vs. 19.10 ± 3.91, p = 0.036). They had significantly greater probing pocket depths (PPD: 3.24 mm ± 0.71 mm vs. 2.7 mm ± 0.37 mm, p < 0.001) and bleeding on probing (BOP: 34.52% ± 22.03% vs. 22.85% ± 17.94%, p = 0.003) compared to controls, but showed no significant difference in clinical attachment level or staging of periodontitis. The OHIP-G14 sum score was significantly higher in COPD patients (7.40 ± 7.28 vs. 3.63 ± 4.85, p = 0.002). Common risk factors such as educational status, physical activity, dentist visit frequency, oral hygiene regimens and dietary habits were less favourable in patients with COPD. Conclusions COPD was significantly associated with higher tooth loss, PPD, BOP and DMFT besides lower OHRQoL.